CEO and Firm Performance: Indonesian Evidence - Indrawati, Novita; Zarefar, Arumega (Journal of Accounting Research, Organization and Economics, 2024)
Objective This study aims to empirically examine the effect of CEO tenure and CEO work experience on firm performance.Design/Methodology Ordinary least square (OLS) is used as an analytical technique to test the research hypothesis. This research sample consists of companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, with 451 total observations. We conduct robustness tests using alternative measurements for the dependent variable to prove that the results of this study are robust.Results The study's key findings are as follows: CEO tenure is found to have a detrimental effect on firm performance. In contrast, CEO work experience is shown to impact firm performance positively.Novelty/Originality To the author's knowledge, research that distinguishes between tenure and CEO work experience and its effect on firm performance is still scarce, especially in the Indonesian context. This study opens a new perspective on the experience of a CEO who is seen not only by working time but also by the number of companies he has led.